Ultrasonic diagnostics of vascular complications after laser procedures - I. N. Bondarenko (Инновационная медицина Кубани)
A clinical case of treatment of rosacea with a high-intensity laser at different stages, performed under control of high-resolution ultrasound (HRU), is presented. According to clinical guidelines, patients in the erythematous stage of rosacea (stage I) undergo selective coagulation of superficial vessels with a neodymium laser. Diagnosis and determination of the severity of the disease are carried out based on the presence of primary and secondary elements of the rash. There are no criteria for ultrasound assessment of the skin and its vascularization in patients with rosacea. During ultrasound examination after 4 laser procedures in B-mode, the dermis is heterogeneous due to hypoechoic papillary and hyperechoic reticular layers, without signs of infiltrative changes, in the color Doppler mapping mode there is a pronounced vascularization of the papillary dermis in the area of interest, represented by multiple vessels in contrast to single vascular structures seen on ultrasound after two laser treatments. According to the results of ultrasound examination, a more severe degree of the disease was diagnosed, which served as the basis for prescribing therapy with systemic retinoids. Clinical observation demonstrates the capabilities of ultrasound in planning laser procedures in order to reduce the risk of complications, their early diagnosis and monitoring of treatment if they occur.